Hubungan Intensitas Penggunaan AI dengan Indeks Keahlian Digital dan Keterampilan Abad 21 Mahasiswa UIN Syarif Hidayatullah Jakarta - Hilma, Hidayatul Maslakha; Choiriyah, Siti; Nisa, Sifa Khoridatun; Firdaus, Ahmad (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to examine the relationship between the intensity of using Artificial Intelligence (AI) technology and the digital skill index and 21st-century skills of students at UIN Syarif Hidayatullah Jakarta. This quantitative study uses a survey method with a questionnaire distributed to students. T-tests were used to examine the relationship between AI usage and both variables, while an F-test was used to examine the simultaneous relationship. The results of the T-test show a significant relationship between AI usage intensity and the digital skill index (t = 5.34, p < 0.01) and 21st-century skills (t = 4.78, p < 0.01). The F-test results show a significant simultaneous effect between AI usage intensity and both variables (F = 8.76, p < 0.01). Overall, the findings of this study indicate that AI usage can enhance students' digital skills and 21st-century skills, which are essential for academic and professional success in the digital era.